Depression level and quality of life in ovarian cancer patients in Zainoel Abidin Hospital, Banda Aceh - Ghina Akmalia; M Riswan; M Andalas (Universitas Airlangga, 2017)
Objectives: to determine the relationship between depression and quality of life in ovarian cancer patients who are undergoing chemotherapy in RSUDZA Banda Aceh.Materials and Methods: This study was an analytical observa-tional study with cross-sectional design approach. The samples were taken by using accidental sampling with total of respondents are 30 patients. Depression level was assessed by using the BDI-II questionnaire and quality of life was assessed by using the EORTC QLQ-C30 questionnaire. Then, data were analyzed by using Spearman’s Correlation test.Results: The most of the cases were no depression (53,3%), and good quality of life (56,7%). The lowest cases were patients with severe depression (6,7%), and poor quality of life (16,7%). The results of data analysis obtained p value=0.000 (p≤0,05). Conclusion: there is a significant relationship between depression and quality of life in ovarian cancer patients who are undergoing chemotherapy in RSUDZA Banda Aceh.